Kajian Konsep Arsitektur Dekontruksi Pada Bangunan Walt Disney Concert Hall, Los Angeles - Jumastan, Jumastan; Prayogi, Lutfi (Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the application of the deconstructivist architectural concept, which emphasizes aesthetics to create dynamic and unexpected spatial experiences. Unlike modern architecture, which emphasizes simplicity, deconstruction introduces asymmetrical, distorted forms that challenge conventional design logic. Applying this concept to performance buildings presents challenges, as these buildings require spatial stability and layouts that support their functional elements. This research aims to explore the application of deconstruction principles and identify key design elements in performance buildings. Using a descriptive qualitative method based on documentary studies, this research analyzes the design elements and principles of deconstruction. The findings reveal that the core principles of deconstruction include instability, irregularity, impurity, disharmony, fragmentation, fluidity, metaphor, distortion, and contrast. A case study of the Walt Disney Concert Hall demonstrates fluidity and distortion through its curved forms and reflective titanium materials. This study concludes that while deconstructivist architecture often features unconventional forms, its application in performance buildings successfully integrates aesthetics and spatial functionality to enhance user experience.